Dialogues with the dead: the discussion of mortality among the Sora of eastern India - Vitebsky, Piers (New Delhi, 1993)
Piers Vitebsky's study of religion and psychology in tribal India focuses upon a unique form of dialogue between the living and the dead which is conducted through the medium of a shaman in trance. The dead sometimes nurture their living descendants, yet at the same time they inflict upon them the very illnesses from which they themselves have died. Through intimate dialogue, the Sora use the occasion of death to explore their closest emotional attachments in all their ambivalence. Dr Vitebsky analyses the actors' words and relationships over several years and develops a typology of moods among the dead and kinds of memory among the living. In comparing Sora shamanism with the treatment of bereavement in psychoanalysis and psychotherapy, he highlights a contrast in their assumptions which has far-reaching consequences for the social and professional scope of the two kinds of practice.
Keywords: Tribes Eastern India